A review of actuation and power electronics options for flapping-wing robotic insects - Karpelson, M.; Gu-Yeon Wei; Wood, R.J. (2008 IEEE International Conference on Robotics and Automation, 2008)
Flapping-wing robotic insects require actuators with high power densities at centimeter to micrometer scales. Due to the low weight budget, the selection and design of the actuation mechanism needs to be considered in parallel with the design of the power electronics required to drive it. This paper explores the design space of flapping-wing microrobots weighing lg and under by determining mechanical requirements for the actuation mechanism, analyzing potential actuation technologies, and discussing the design and realization of the required power electronics. Promising combinations of actuators and power circuits are identified and used to estimate microrobot performance.